Bridging informal and formal science learning through home gardening during COVID-19: An experiential approach to environmental education - Nanda, Appaji; Janardhana, Gungurumale L. (Education and Development Research, 2025)
Formal education is curriculum-oriented with less practical exposure or time limit to practice, informal learning is life skills learning education since childhood from their parents and society. The COVID-19 pandemic and school closures indicate a loss of formal education and learning deficiency, knowledge, and skill gaps, which are the universal challenges for every teacher, parent, and student. Hence the present study explores to understand the activities of the garden activities to connect with textbook concepts. We interacted with 8923 students of Lower primary school, Higher primary school, and High school and 24,255 family members. The collected data from the semi-structured questionnaire for the students and family responses were analysed with descriptive and qualitative statistics. The findings revealed that the involvement was more with Lower primary school than Higher primary school and High school. The different classes of students, like the Lower primary school (rs = 0.85, p<0.003)involvement ratio, have a higher significance than Higher primary school (rs = 0.72, p<0.05) and High school (rs = 0.65, p<0.05). The significant involvement of parents revealed that the father gave more exposure to the skills than the mother. Whereas High school students experience and gain more skill knowledge for the textbook content concept was ideal than Higher primary school and Lower primary school. Further research can be focused on studying the impact of pedagogical links with home gardening and farming skills serve as an effective module to connect informal learning with formal education, with a modification in education curriculum and policy.